Space flight dynamics - Kluever, Craig A. (Aerospace series (Chichester, England), 2018)
With practical, real-world examples illustrating key concepts throughout, this concise resource provides thorough coverage of space flight topics with self-contained chapters serving a variety of courses in orbital mechanics, spacecraft dynamics, and astronautics. --